2020
DOI: 10.1002/brb3.1933
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in agenesis of the corpus callosum: Working memory and sustained attention in the BTBR inbred mouse strain

Abstract: Introduction Agenesis of the corpus callosum (AgCC) is characterized by the congenital partial or complete absence of the corpus callosum. Several strains of mice have been reported to carry AgCC, with the BTBR T+Itpr3tf/J (BTBR) inbred mouse strain consistently showing a complete absence of the corpus callosum, as well as a variable reduction in the size of the hippocampal commissure. While much research has focused on the social deficits of the BTBR strain, little research on its cognitive behavior has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…For these reasons, physically cutting only the HC is nearly impossible in rats. One alternative would be to use a species that is genetically deficient in the commissural fibers, such as the BTBR mice [24,25]. However, this approach might be inappropriate because it does not exclude the possibility of compensation by other brain regions or neural circuits, and it would need to be performed in wild-type animals.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, physically cutting only the HC is nearly impossible in rats. One alternative would be to use a species that is genetically deficient in the commissural fibers, such as the BTBR mice [24,25]. However, this approach might be inappropriate because it does not exclude the possibility of compensation by other brain regions or neural circuits, and it would need to be performed in wild-type animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings are in good concordance with evidence of anxiolytic-like properties of BDNF, including results obtained in animals with an autistic-like phenotype. It could be suggested that the local increase in BDNF expression in the hippocampus partially corrects neuronal deficit in the corpus callosum observed both in ASD patients [95] and BTBR mice [94] that results in the amelioration of anxiety and stereotypical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ASD is characterized by an increase in brain volume due an abnormal cortical overgrowth pattern and by increases in size, spine density, and neuron population that leads to the dysregulation of postnatal synaptic pruning and results in a huge variety of forms and degrees of signal-over-noise discrimination losses [87]. On the other hand, BTBR mice also demonstrate a similar spectrum of neuromorphological abnormalities [88][89][90][91][92][93] including the absence of corpus callosum [94], known for ASD patients [95]. Thus, we can hypothesize that a BDNF-induced increase in neurogenesis and axonal growth may exert diverse effects on autistic-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the core symptoms of ASD, BTBR mice also display learning and memory impairments in various settings (240)(241)(242). Several histological observations and MRI assessments support separated hippocampal commissure and increased hippocampal volume in BTBR mice relative to controls, and these anatomical changes may underlie their behavioral phenotypes (243)(244)(245)(246). Moreover, the hippocampus has lower 5-HT, acetylcholine, dopamine, and histamine content in the BTBR animals than in the C57BL/6J strain (246-248).…”
Section: Btbr Animal Modelsmentioning
confidence: 93%